Ẓāhiratu at-Tanāṣ ad-Dīnī fī Riwāyah al-Qāhirah al-Jadīdah li-Najīb Maḥfūẓ: Dirāsah Waṣfiyyah Taḥlīliyyah - Zabidin, Mohd Azizul Rahman bin; Eldesoky, Ebrahim Mohammad Ahmad (Middle Eastern Culture & Religion Issues, 2024)
The concept of religious intertextuality involves the integration of selected religious texts, whether from the Holy Quran or the noble Prophetic Hadith, into the original text of a novel. These texts are carefully chosen to harmonize with the narrative context and serve a cognitive or artistic purpose. It is undeniable that the Holy Quran and the Prophetic Hadith are among the most significant sources that both ancient and contemporary novelists have drawn inspiration from, prominently featuring them in their creative works. Consequently, this research aims to investigate the phenomenon of religious intertextuality in Naguib Mahfouz's novel al Qahira al Jadida (Cairo Modern), intending to comprehend the reason for its employment within the novel's texts. The research follows a descriptive-analytical statistical methodology. Among the key findings are that Naguib Mahfouz was significantly influenced by Islamic culture, as evidenced by his extensive incorporation of religious texts from the Holy Quran and the Prophetic Hadith in al Qahira al Jadida. This influence extends to shaping the events and narrative structure, enriching the fictional texts to generate new meanings. The results also suggest that creative writing critically depends on such literary vitality derived from the mechanism of interweaving and blending known texts, known as intertextuality. This process proves to be a crucial and dynamic tool for both authors and readers alike.